Composition and amount of nutrients entering the soil with cotton biomass and green manure - et. al., Hasanova Aynur Oruj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The experience of developed countries in the field of agriculture and research results show that high efficiency from mineral fertilizers can be obtained on fertile soils. That is, the soil should contain a large amount of organic substances, microelements, beneficial microorganisms, various enzymes that activate microbiological processes, normalize and optimize the nutritional, thermal and water-physical properties of the soil. This can be achieved by regularly applying crop residues and organic fertilizers to the soil. Siderata - green fertilizers - are of great importance for increasing soil fertility.